International Glaciological Expedition to Greenland, 1957–60: Operations in 1957 (Polar Record, 1958)
An international glaciological expedition to Greenland (E.G.I.G.), in connexion with the glaciological programme of the International Geophysical Year, is being sponsored by the International Commission on Snow and Ice. The nations taking part are Denmark, France, Germany and Switzerland. The expedition is to be led by Paul-Emile Victor, and organized by Expéditions Polaires Françaises. The special committee for the expedition consists of Professor R. Haefeli, President, R. Finsterwalder, Vice-President, M. A. Bauer, Secretary, B. Brockamp, Borge Fristrup, F. Kobold, Helge Larsen, J. Martin and P.-E. Victor.